Developing networks in disempowered communities: Experiencing hardships while focusing on opportunities. (12th April 2019) - Stauss, Kimberly; Jackson, Brandon A.; Maxwell, December
Abstract: This study aims to present an evaluation and the process steps of a community‐based initiative (CBI) consisting of a group of organizations that work to enhance the lives of boys and men of colour. Using a participatory research model, the researchers collaborated with 14 community stakeholders to develop the questions during two data collection periods and reviewed the reports for accuracy. The findings were separated into two broad categories. The perceived challenges included a lack of clear goals and measurements of success, an absence of leadership and direction, and a shortage of resources. The successes included passion of partners, increased collaboration, and increasing and maintaining social capital within the community. The lessons learned from both data collection periods helped this CBI broaden its reach and collaboration efforts. Overall, this study provides suggestions to other CBIs as they embark on making changes in their own communities.